ANTAGONISM DUBOIS IN MODERN CONDITIONS - A. Zaitsev; N. Kotelevskaia; O. Boichenko; A. Nikolishin (Ukrainian Medical Stomatological Academy, 2016)
The article presents the results of research indicators of caries and periodontal tissue status. Part of the research carried out by employees of the Department of Therapeutic Dentistry Higher State Established Educatiuon of Ukraine «Ukrainen Medical Dental Academy». Other studies taken from the literature. Based on these studies we analyzed the compatibility of carious lesions and inflammatory diseases periodontal tissues. The anthropologist Eugene Dubois in the XIX century, examined a large number of ancient human remains. Eugene Dubois found that people prone to periodontal disease, caries disease did not get sick. If the person had periodontitis, this person is not sick tooth decay. This phenomenon was named in his honor antagonism Dubois. The study found that the antagonism Dubois modern humans ceased to be observed. Large numbers of people sick and caries disease and periodontal disease. Studies show that a combination of caries disease and periodontal diseases in humans is observed everywhere. Some studies fall within the normal distribution. This makes them statistically significant. The combination of caries diseases and periodontal diseases in humans occurs in different geoetnoclimatic zones. The combination of caries diseases and periodontal diseases in humans occurs when exposed to various environmental factors. The combination of caries diseases and periodontal diseases in humans is observed at all possible mind states of human. The combination of caries diseases and periodontal diseases in humans is observed at all possible somatic states of human. Some studies show on the common microbial factor in the occurrence of caries diseases and inflammatory diseases of the periodontal tissues. The generality of the microbial factor in the occurrence of caries diseases and inflammatory diseases of the periodontal tissue draws attention to ways of coexistence of microorganisms that cause cavities and periodontal disease. The generality of the microbial factor in the occurrence of these diseases draws attention to ways of coexistence of microorganisms that cause cavities and periodontal disease. The dependence of the incidence from living conditions is the need to consider these factors when predicting the prevention and treatment of dental caries and periodontal disease.